Waterborne antimicrobial resistance in India: strategies to address the key challenges and gaps through a One Health approach - Yadav, Shweta; Mateo-Sagasta, Javier; Graham, D.; Moodley, Arshnee; Jampani, Mahesh; Joshi, H.; Hazra, S.; Sikka, Alok (International Water Management Institute, 2025)
Antimicrobial Resistance (AMR) has become a “silent pandemic,” projected to surpass cancer as the leading cause of global deaths by 2050. India faces one of the world’s highest AMR-related mortality rates, driven by the overuse of antibiotics across human health, livestock, agriculture, and aquaculture, leading to widespread contamination of surface water and groundwater. Although India has launched several initiatives—including the National Action Plan on AMR (NAP-AMR) and the National One Health Mission (NOHM)—water, a major carrier of AMR, remains insufficiently addressed in national and state strategies.